Development of ceramic water filter (CWF) for point-of-use household water filtration system using nanotechnology - Tiu, Sicily B. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
In this study, candle type ceramic water filter for point-of-use household filtration system was developed to significantly improve the anti-microbial quality of household water thereby reducing the risk of different waterborne diseases. Nanotechnology was applied by incorporating silver nanoparticles and polyelectrolyte multilayers to clay ceramic support. Grog and ceramic support formulation, firing temperature and time were determined to give maximum desirability. Based from the porosity tests conducted, the 70% rice hull ash and 30% terracotta was considered the best grog formulation for the filter and the 55% grog and 45% terracotta clay was the chosen formulation for the final ceramic support. The molder design for the fabrication of the standardized candle type ceramic water filter (CWF) was also developed. From the three mesh sizes (300 µm, 425 µm and 600 µm) of ceramic water filter raw materials (clay and grog) prepared in this study that were subjected into three firing temperatures (800°C, 900°C and 1000°C), it was found out that 600 µm of both clay and grog and firing temperature of 1000°C resulted to a desirable pore size distribution and porosity of 0.896 (Design Expert v.8). Characterizations of fabricated membrane were done and results showed that the multilayer ultrathin films and silver particles were stable and homogenous on the clay ceramic support. It also resulted to a highly porous membrane with high thermal resistance and with enhanced antimicrobial properties. The fluid consistency indices (K) of the different types of water samples were also determined. All the filtration samples showed that none of the models yield a constant K which means that the behavior of the fluid passing through the clay ceramic-polyelectrolyte multilayer-AgNPs hybrid model system was non-Newtonian and can be considered non-Darcian since Darcy's law is restricted to Newtonian fluids only. However considering the quadratic equation of the plot, cake filtration is the most probable filtration mechanism for the clay ceramic-polyelectrolyte multilayer-AgNPs hybrid model system.
Dissertation (Ph.D. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Sanitation, Household; Water -- Purification -- Filtration; Nanotechnology